Computer systems organization and architecture - Carpinelli, John D. (Singapore : Pearson Education Asia Pte. Ltd., 2002)
This book provides up-to-date coverage of fundamental concepts for the design of computers and their subsystems. It presents material with a serious but easy-to-understand writing style that makes it accessible to readers without sacrificing important topics. The book emphasizes a finite state machine approach to CPU design, which provides a strong background for reader understanding. It forms a solid basis for readers to draw upon as they study this material and in later engineering and computer science practice. The book also examines the design of computer systems, including such topics as memory hierarchies, input/output processing, interrupts, and direct memory access, as well as advanced architectural aspects of parallel processing. To make the material accessible to beginners, the author has included two running examples of increasing complexity: the Very Simple CPU, which contains four instruction sets and shows very simple CPU design; and the Relatively Simple CPU which contains 16 instruction sets and adds enough complexity to illustrate more advanced concepts. Each chapter features a real-world machine on which the discussed organization and architecture concepts are implemented. This book is designed to teach computer organization/architecture to engineers and computer scientists.
Ch. 1. Digital Logic Fundamentals -- Ch. 2. Introduction to Finite State Machines -- Ch. 3. Instruction Set Architectures -- Ch. 4. Introduction to Computer Organization -- Ch. 5. Register Transfer Languages -- Ch. 6. CPU Design -- Ch. 7. Microsequencer Control Unit Design -- Ch. 8. Computer Arithmetic -- Ch. 9. Memory Organization -- Ch. 10. Input/Output Organization -- Ch. 11. Reduced Instruction Set Computing -- Ch. 12. Introduction to Parallel Processing.
Includes index.
Keywords: COMPUTER ORGANIZATION